Gambaran Tingkat Kecemasan Pasien Pre Operasi di RSU Mayjen H.A Thalib Kerinci - Azma Ulia (Malahayati Nursing Journal, 2022)
ABSTRACT:OVERVIEW OF PREOPERATIVE PATIENT'S ANXIETY LEVEL AT MAJOR GENERAL H.A THALIB KERINCI HOSPITAL Introduction: Pre-surgery is the time before surgery to prepare the patient for surgery both physically and psychologically. Patients before surgery will experience anxiety. Anxiety is an emotion and subjective experience of a person associated with feelings of uncertainty and powerlessness such as fear and worry. Purpose: This study aims to determine the description of anxiety level of preoperative patients at RSJ Major General H.A Thalib Kerinci Year 2021. This type of research is qualitative research with a descriptive research design. The population in this study from January to February 2021 is as many as 518 patients and the sample in this study is as many as 84 patients. The sampling technique uses accidental sampling. The data were analyzed univariate. The measuring tool used is the HARS (Hamilton Anxiety Rating Scale) questionnaire to measure preoperative patient’s anxiety levels.Result: This research was conducted at Operation Room of Major General Hospital HA Thalib Kerinci for 1 month. The result showed that the number of respondents with mild anxiety 39 people (46,4%), moderate anxiety 40 people (47,6% ), severe anxiety 5 people (6%), no one experiencing panic anxiety, and no one is not anxious. Conclusion: This study illustrates that most of the preoperative patients at Major General H.A Thalib Kerinci Hospital are in good psychological condition to face the surgery.Keywords: Anxiety level, pre-operation INTISARI: GAMBARAN TINGKAT KECEMASAN PASIEN PRE OPERASI DI RSU MAYJEN H.A THALIB KERINCI Latar belakang : Pre operasi merupakan waktu sebelum dilakukan operasi untuk menyiapkan pasien untuk operasi baik secara fisik maupun psikologis. Pasien sebelum dilakukan operasi akan mengalami kecemasan. Kecemasan adalah sebuah emosi dan pengalaman subjektif dari seseorang yang berkaitan dengan perasaan yang tidak pasti dan tidak berdaya seperti rasa takut dan khawatir. Penelitian ini bertujuan untuk mengetahui gambaran tingkat kecemasan pasien pre operasi di RSU Mayjen H.A Thalib Kerinci Tahun 2021.Metode penelitian :Jenis penelitian ini adalah penelitian kualitatif dengan desain penelitian deskriptif. Populasi pada penelitian ini dari Januari- Februari 2021 sebanyak 518 pasien dan sampel pada penelitian ini sebanyak 84 pasien. Teknik pengambilan sampel menggunakan accidental sampling. Adapun data dianalisa secara univariat. Alat ukur yang digunakan adalah kuesioner HARS (Hamilton Anxiety Rating Scale) untuk mengukur tingkat kecemasan pasien pre operasi. Penelitian ini dilakukan di Ruang operasi RSU Mayjen H.A Thalib Kerinci selama 1 bulan dari tanggal 15 Februari sampai 15 Maret 2021.Hasil; Hasil penelitian menunjukkan bahwa jumlah responden dengan kecemasan ringan 39 orang (46,4 %), kecemasan sedang 40 orang (47,6 %), kecemasan berat 5 orang (6 %), tidak ada yang mengalami kecemasan panik dan tidak ada yang tidak cemas.Kesimpulan:  Penelitian ini menggambarkan bahwa sebagian besar  pasien pre operasi di RSU Mayjen H.A Thalib Kerinci berada dalam kondisi psikologis yang cukup baik untuk menghadapi operasi.Kata kunci : Tingkat kecemasan, pre operasi